Pendekatan Manajemen Mutu Terpadu Untuk Meningkatkan Kualitas Proses Belajar Mengajar - Hutagamissufardal Hutagamissufardal (INFO-TEKNIK, 2005)
Teaching learning process is a very important aspect in university education system. The method of student in learning a subject depends on the method of lecturer in teaching their student. In fact, teaching learning process in class has usually never been evaluated by the lecturer. Lecturer generally evaluates only student’s examination results. Evaluation of student’s examination result indicates that the quantity of student who passes the examination and the quality of their achievement index are very low. The aim in this teaching grant activity is to improve the quality of teaching learning process. Benefit expected from this activity is to improve the quality and quantity of student’s graduation in Mathematics 1st subjectThe activities are started with the preparation of instructional material in the beginning of semester. The components are Outline of Lecture Instruction (GBPP), Set of the Lecture Event (SAP), teaching contract, assignment documents, mid term and final examination documents, and lecture note. In one semester intercourse, based on the result of mid term examination, lecturer is performing personal approach to the unsatisfactory student. The evaluation result of student’s answer sheet is also returned as part of teaching learning process. Assignment counselling is also conducted for the student in class to improve their competence by involving them. It certain intercourse, questionnaires is given to student as the source of information for the lecturer to evaluate his teaching learning processThe results of teaching grant activities show that by improving teaching learning process, the quality and quantity of graduated students in Mathematics 1st subject are also improved.